Resource Rehabilitation with Rural Development: the New JFM Paradigm - Singh, T. P.; Datta, Suman; Varalakshmi, V. (Indian Forester, 2001)
Joint Forest Management (JFM) experiences in India have revealed the crucial role that social and economic incentives play in sustaining these efforts. JFM was conceived as a sustainable management system based on active participation of forest fringe dwellers whose opportunity cost was compensated by giving some rights and privileges on forest products. However, the definition and scope of the JFM programme is being expanded from rehabilitation of degraded forest lands to socio-economic development of resource-dependent communities; from managing resources for meeting peoples’ demand for forest products to managing pressures through alternatives. The purpose of this paper is two fold: (i) to assess the extent to which the sustainability of JFM programme is dependent on rural development and (ii) to evaluate the extent of effects of already taken rural development efforts in four States under JFM namely Andhra Pradesh, Haryana, Madhya Pradesh and West Bengal. It is seen that from a forest resource management programme, States have adopted an integrated approach of rural development to supplement forest protection measures. The emphasis is now on meeting the social, economic and human development needs of communities. The village-level institutions created for natural resource management are also emerging as the focal point for rural development and each of these functions is mutually enriching and supportive. The paper traces this paradigm shift, ably supported by examples from across the country to present the crucial role for socio-economic development of communities for sustaining join forest management initiatives. It emphasises that a self-reliant community is a prerequisite for sustaining forests and should be the basic philosophy for community Forestry Programme.